Análise do impacto do desenvolvimento baseado em modelos na produção de software aviônico - Mottin, Gustavo Giroletti; Porto, Josiane Brietzke (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2019: Anais do XV Simpósio Brasileiro de Sistemas de Informação, 2019)
Normally, the development of avionics software as part of embedded systems follows guidelines defined by the industry that defines objectives and activities that are critical for enabling and approval for operation. The DO-331 is one out of these guidelines recently published that refers to the usage of model-based development. This article presents a survey, done with 79 specialists working in the area, in international level, looking forward to gather perceptions about the impact of model-based development in avionics software production. The results points out that using the methodology normally is beneficial, especially in some development steps, where these might be augmented or diminished according to how it is applied by the organization.